Persepsi Mahasiswa Terhadap Whistleblowing System Sebagai Upaya Pencegahan Academic Fraud - Nia Dewi Kurniawati; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The study has served to identify the student's perceptions of the whistleblowing system as an effort to prevent academic fraud, to explain frequent academic cheating among university students to reduce the level of academic fraud, and to illustrate the system's working process. The study involves a qualitative approach. The respondents used in this study are students of a moderate or former core study program of student activities and charitable organizations in the STIE PGRI Dewantara Jombang ward. The result of this study is that academic fraud can be prevented, reduced, and detected by this system. It can be caused by pressure, threats, and insecurity that can have a real deterrent to both the perpetrator and the potential academic fraud by applying the system. For the whistle to run optimally, it should be supported by the entire academic facility. So it can create a conducive environment in a college environment that can enhance both the quality of education and its graduates.